Single-Case Analysis to Determine Reasons for Failure of Behavioral Treatment via Telehealth. (March 2018) - Schieltz, Kelly M.; Romani, Patrick W.; Wacker, David P.; Suess, Alyssa N.; Huang, Pei; Berg, Wendy K.; Lindgren, Scott D.; Kopelman, Todd G.
Functional communication training (FCT) is a widely used and effective function-based treatment for problem behavior. The purpose of this article is to present two cases in which FCT was unsuccessful in reducing the occurrence of problem behavior displayed by two young children with an autism spectrum disorder. Both children received the same functional analysis plus FCT treatment package via telehealth that had proven to be highly successful for the other participants. The FCT package was conducted within tightly controlled single-case designs for each participant, which permitted subsequent analyses to determine why FCT was unsuccessful. These analyses suggested distinct reasons for the treatment failure for each child. Although the negative results of treatment appeared to be similar for both children, the specific reasons for treatment failure were highly individualistic and identifiable via the single-case analyses conducted. We present findings from both our initial and subsequent analyses and discuss the implications.